FAKTOR FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN DAERAH MALUKU (Studi Empiris di SKPD Pemerintah Daerah Propinsi Maluku) - Theresia F. Sitanala (Soso-Q : Jurnal Manajemen, 2017)
Present research is proposed to examine empirically the influences of human resource capasity, utilization of information technology, internal control of accounting over value of information of local financial reporting information. Technical sampling is performed using purposive sampling with criteria of employees (head and staff) of financial administration in SKPD Maluku Province. 100 respondents are asked to fill questioner which taken as primary data. Hypothetical analysis is performed by SPSS program.Empirically, the result present that capacity of human resource did not significantly affect the value of the area of financial reporting information. While the use of information technology and accounting internal controls significantly affect the value of the area of financial reporting information. Keywords: human resource capacity, utilization of information technology, internal control of accounting,  the area of financial reporting information